The impact of metabolic syndrome on metabolic, pro-inflammatory and prothrombotic markers according to the presence of high blood pressure criterion - Juliana S. Gil; Luciano F. Drager; Grazia M. Guerra-Riccio; Cristiano Mostarda; Maria C. Irigoyen; Valeria Costa-Hong; Luiz A. Bortolotto; Brent M. Egan; Heno F. Lopes (Clinics, 2013)
OBJECTIVES: We explored whether high blood pressure is associated with metabolic, inflammatory and prothrombotic dysregulation in patients with metabolic syndrome. METHODS: We evaluated 135 consecutive overweight/obese patients. From this group, we selected 75 patients who were not under the regular use of medications for metabolic syndrome as defined by the current Expert Panel on Detection, Evaluation and Treatment of High Blood Cholesterol in Adults criteria. The patients were divided into metabolic syndrome with and without high blood pressure criteria (≥130/≥85 mmHg). RESULTS: Compared to the 45 metabolic syndrome patients without high blood pressure, the 30 patients with metabolic syndrome and high blood pressure had significantly higher glucose, insulin, homeostasis model assessment insulin resistance index, total cholesterol, low-density lipoprotein-cholesterol, triglycerides, uric acid and creatinine values; in contrast, these patients had significantly lower high-density lipoprotein-cholesterol values. Metabolic syndrome patients with high blood pressure also had significantly higher levels of retinol-binding protein 4, plasminogen activator inhibitor 1, interleukin 6 and monocyte chemoattractant protein 1 and lower levels of adiponectin. Moreover, patients with metabolic syndrome and high blood pressure had increased surrogate markers of sympathetic activity and decreased baroreflex sensitivity. Logistic regression analysis showed that high-density lipoprotein, retinol-binding protein 4 and plasminogen activator inhibitor-1 levels were independently associated with metabolic syndrome patients with high blood pressure. There is a strong trend for an independent association between metabolic syndrome patients with high blood pressure and glucose levels. CONCLUSIONS: High blood pressure, which may be related to the autonomic dysfunction, is associated with metabolic, inflammatory and prothrombotic dysregulation in patients with metabolic syndrome.